The post - conflict and public spending: a challenge for Colombia (2015)
Historically some countries of the world have gone through wars and internal and external armed conflicts, a situation in which they have been involved Central American countries like El Salvador which has wanted to do a compilation of their experiences to the process of post-conflict to take them Colombia as a benchmark for what can come from signing the current peace process forward with the Farc in Havana - Cuba. Facts about the violence and the internal armed conflict that Colombia has suffered negatively marked its history, directly affecting society which has been exposed to issues such as displacement, massacres, dispossession of land and extortion among analyzes others; likewise an outline on the effects that violence has produced economic and productive development of the country, slowing foreign and local investment, and generating an image of insecurity to the world is made. Finally the challenges which can be seen fronted the country in case of signed peace agreements in Havana, as you will affect public spending and international private partnerships should anticipate in order to finance the process of post observed - conflict, for the sole and primary objective that Colombia finally enjoy peace and a lasting and sustainable peace.